BIOINSEKTISIDA TERHADAP NYAMUK AEDES AEGYPTI BERBAHAN DASAR EKSTRAK ETANOL DAUN SERAI (CYMBOPOGON CITRATUS) - Jennifer Wiranatha; Robby Makimian; Rita Dewi (Bahasa Indonesia, 2021)
Introduction: Dengue hemorrhagic fever is one of the most common infectious diseases in Indonesia. The vector of this disease is Aedes aegypti (Ae. aegypti). Dengue hemorrhagic fever can be controlled by a few measures, one of them is using insecticide. However, frequent use of chemical insecticide could lead to resistance and is harmful to non-target organisms. One of the solutions for this problem is the use of bioinsecticide derived from lemongrass (Cymbopogon citratus or C. citratus) leaves extract. Methods: The design of this study is true experimental post-test only control group. The population used are adult Ae. aegypti mosquitoes. For each experiment, 10 mosquitoes are required and given the extract of C. citratus in 2%, 10%, and 20% concentrations, and negative control respectively.The lethal effect of the extract is observed in 10, 30, 60 minutes and 6, 12, 18, 24 hours. Results: There is a significant difference in the lethal effect of Ae. aegypti mosquitoes with variations in duration of exposure to the C. citratus leaves extract (p = 0.007), but no significant difference with variations in extract concentration given (p = 0.281). Conclusion: C. citratus leaves extract has bioinsecticidal effect on Ae. aegypti mosquitoes. The optimal result of mosquito mortality is achieved by using the extract in 20% concentration with duration of 12 hours.